Pengaruh Kualitas Pelayanan, Kualitas Produk dan Harga Terhadap Kepuasan Pelanggan Lawang Agung Cabang Malang - Elvi Yuli Asriski; N. Rachma; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to examine and analyze the effect of service quality, product quality, and price on customer satisfaction simultaneously or partially. This study used 1000 for its population, and reduced it using the Slovin formula to 91. Data collection used a questionnaire and used SPSS version 21.0 to analyze the data. The sampling technique in this study is by census, then using data testing techniques such as validity test, reliability test, classic assumption test and multiple linear regression analysis and hypothesis testing.The results obtained in this study are that service quality and product quality affect customer satisfaction, while price does not affect customer satisfaction. And simultaneously service quality, product quality and price can affect customer satisfaction Keywords: service quality, product quality and customer satisfaction